ECOPRINT TAS TOTLEBAG KREASI DASAWISMA MANGGIS - Harsanti, Tika Dessy; Chrisdanty, Febry (STIE Malangkucecwara, 2023)
The Malang City Government is very concerned about the potential of women's associations, most of which are engaged in women's empowerment. Today's women not only devote themselves to their families, but also become creative mothers who can earn money even from home. To be able to equip women who are members of the Dasawisma mangosteen women's association to be able to enrich creativity and also increase the business potential that can be run, the service team will provide training on making ecoprint batik using natural colors and using steaming or steam techniques. There are many types of batik making, but ecoprint batik has the advantage that the colors come from various kinds of living plants that are around us as well as the coloring materials which are more environmentally friendly with unique motifs that are popular today.The method used to carry out the training program for making ecoprint batik is to start with theoretical debriefing, which will then be followed by practice on making ecoprint batik using the steaming technique. The two methods above will be followed by all training participants who are expected to provide capital in the form of knowledge for partners to be applied as one of the efforts to empower women in Malang City. Partners during the training carry out with enthusiasm, the knowledge gained can be used as capital to have a creative business at home and the products produced are good enough and will continue to develop expertise and products from partners.